Permainan Tradisional Sebagai Media Warming Up pada Atlet Bola Tangan SKO Riau - Makorohim, M. Fransazeli; Alficandra, Alficandra; Shiddiqy, Muhammad Arsy Ash; Zainal, Zainal; Bintang, Muhammad Ilham; Aulia, Riska (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The training process is sometimes boring for children, the lack of creativity and innovation from the coaches makes children stop training at any time, sometimes the goals and objectives of training have not been achieved children have stopped training because they feel bored. In an effort to eliminate boredom, warming up during the training process can be done through traditional games such as traditional games terompah panjang and gerobak sodor because in addition to being fun, the game also includes many elements of movement, such as running. In addition, traditional games are one of the cultural contents that need to be maintained so that they are not lost. Of course, it is a challenge for traditional games that prioritize the values of responsibility, teamwork, honesty, and even involve nature as their characteristics to remain present in every generation. Traditional games are also expected to be an alternative that can be used as a warm-up medium in a sport with the aim of the values contained in the game can be adopted and applied. In order to achieve this goal, the role of traditional games is very important. It is hoped that this community service activity will increase students' and athletes' insight into the role of traditional games as a warm-up medium for training.